Analysis of English Language Needs in Elementary School in terms of Geographical Aspects - Rahmat Rahmat; Ita Sarmita Samad; Dian Firdiani (Universitas Muhammadiyah Enrekang, 2020)
The status of English lessons in the 2013 curriculum is an alternative extracurricular program. This means that schools are given a policy to choose to teach English as extracurricular program or not. Especially for Enrekang District, Enrekang Regency,many elementary schools chose not to program it. Meanwhile, from a geographical perspective, Enrekang Regency is directly adjacent to Tana Toraja Regency which is an international tourism area. Thus, human resources around the area should be equipped with English skills. The aims of this research are: 1) to analyze the need for English as an extracurricular program in elementary schools in Enrekang Regency in terms of geographical aspects. 2) to identify the learning approach to teach English that is in accordance with elementary school students need in Enrekang Regency in terms of geographical aspects. This study quantitative and qualitative (Mix-Method). The subjects of this study were SDN 41 Enrekang which was determined through purposive sampling technique. Data collection techniques that had been carried out are through questionnaires, in-depth interviews, and documentation studies. The result confirms that English is really needs to be programmed as an extracurricular activity in elementary schools. In addition, both behaviorism and cognitive learning approach can be applied in teaching English in this context. The methods and techniques that can be applied should be consistent with that learning approach and match with the students’ actual English needs in a geographical perspective.